DOI: 10.1007/978-3-540-85886-7_33
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Audio Steganalysis Based on High-Order Statistics of a Distortion Measure with Hausdorff Distance

Abstract: Abstract. Steganography can be used to hide information in audio media both for the purposes of digital watermarking and establishing covert communication channels. Digital audio provides a suitable cover for highthroughput steganography as a result of its transient and unpredictable characteristics. Distortion measure plays an important role in audio steganalysis -the analysis and classification method of determining if an audio medium is carrying hidden information. In this paper, we propose a novel distorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In this paper, we will embed digital watermark into audio signal by utilizing the higher-order statistics. The higher order statistics can be obtained in wavelet domain by two steps [27,28]: Hausdorff distance estimation, and higher-order statistics computation.…”
Section: Higher-order Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, we will embed digital watermark into audio signal by utilizing the higher-order statistics. The higher order statistics can be obtained in wavelet domain by two steps [27,28]: Hausdorff distance estimation, and higher-order statistics computation.…”
Section: Higher-order Statisticsmentioning
confidence: 99%
“…Since the distortion metric should be sensitive to the presence of the watermark and its reaction should be proportional to the embedding strength, Hausdorff distance [27,28] is used as a dissimilarity measure. Among dissimilarity measures over binary images, the Hausdorff distance has often been used in the content-based retrieval domain and is known to have successful applications in object matching.…”
Section: Higher-order Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, audio quality metrics (AQM) were used for differentiating between covers and stegos [5]. Another work argued that AQM are not suitable for steganalysis and instead used Hausdorff distance [6]. Work of [7] showed that features extracted from second order derivative of signals are more significant.…”
Section: Introductionmentioning
confidence: 99%